2004
DOI: 10.2514/1.2983
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Geometric Parameters on Simplex Atomizer Performance

Abstract: A computational analysis of flow in simplex fuel atomizers using the arbitrary-Lagrangian-Eulerian method is presented. It is well established that the geometry of an atomizer plays an important role in governing its performance. We have investigated the effect on atomizer performance of four geometric parameters, namely, inlet slot angle, spin chamber convergence angle, trumpet angle, and trumpet length. For a constant mass flow rate through the atomizer, the atomizer performance is monitored in terms of dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 9 publications
(17 reference statements)
1
30
0
1
Order By: Relevance
“…The size of the recirculation region and the direction of circulation of the liquid depend on the inlet conditions. Thus, this direction is opposite in the simulations of Jeng et al (1998), Yule & Chinn (2000) and Xue et al (2004), in which the liquid is injected with a radial velocity component, and in those of Nouri-Borujerdi & Kebriaee (2012), in which it is injected with an axial velocity component. Nevertheless, such large differences do not seem to have a large effect on the characteristic of the atomizer, probably because the velocity components of the recirculating flow in an axial section of the chamber are small compared to the azimuthal velocity in other regions of the chamber and to the velocity around the orifice.…”
Section: Viscous Effectsmentioning
confidence: 90%
See 1 more Smart Citation
“…The size of the recirculation region and the direction of circulation of the liquid depend on the inlet conditions. Thus, this direction is opposite in the simulations of Jeng et al (1998), Yule & Chinn (2000) and Xue et al (2004), in which the liquid is injected with a radial velocity component, and in those of Nouri-Borujerdi & Kebriaee (2012), in which it is injected with an axial velocity component. Nevertheless, such large differences do not seem to have a large effect on the characteristic of the atomizer, probably because the velocity components of the recirculating flow in an axial section of the chamber are small compared to the azimuthal velocity in other regions of the chamber and to the velocity around the orifice.…”
Section: Viscous Effectsmentioning
confidence: 90%
“…Comparisons were made with predictions of irrotational theories and correlations derived by Rizk & Lefebvre (1985). In two follow-up works, Sakman et al (2000) and Xue et al (2004) numerically explored and rationalized the dependence of the atomizer characteristics on geometrical parameters not accounted for by irrotational models. The effects of various geometrical parameters and of the Reynolds number on the size of the air core and other characteristics of the atomizer have also been investigated by Haider, Dash & Som (2003) and Nouri-Borujerdi & Kebriaee (2012), while Steinthorsson & Lee (2000), Hansen et al (2002), , and von Lavante, have carried out three-dimensional and non-stationary flow computations.…”
Section: Introductionmentioning
confidence: 98%
“…Giffen and Muraszew [31] conducted measurements with a number of swirl atomizers which showed that their inviscid theory predicted the trends in the dependence of atomizer constant on performance parameters reasonably well. More recently, Xue et al [34] carried out inviscid analysis for newer atomizer geometries that include a trumpet and have inlet angle (β) that may vary from 0 to 90 degrees. The qualitative behavior of film thickness, spray cone angle, and discharge coefficient predicted by their analysis agrees well with detailed computational simulations [34,35,36].…”
Section: Figurementioning
confidence: 99%
“…Detailed comparison of experimental measurements/empirical correlations [46,47,48] and computational results was carried out which showed excellent agreement. The validated computational code was then used to investigate the effects of atomizer geometry under two flow regimes -constant mass flow rate through the atomizer [34,36,45,49] and constant pressure drop across the atomizer [35].…”
Section: Figurementioning
confidence: 99%
“…Based on the results of 9 test cases with different design parameters, it is found that the best location of tangential slot is at the radial location of 1/2 or 3/4 cone's radius, while its tilt angle is 20°. 。 对于离心式喷嘴内部结构的研究,国外学者 XUE 等 [12] 利用数值方法研究 90°到 180°的喷嘴内部 锥形室锥角,发现其对雾化锥角 [13] 的影响较小,但 会改变液体薄膜的厚度;关于燃用重油的两相流喷 嘴,FERREIRA 等 [14] 通过试验探究了影响其喷射效 果的重要设计参数;SAKAMEN [15] 通过任意拉格朗 日一欧拉方法探究喷嘴旋流室、出口的长径比等各 个参数之间的关系对雾化效果的影响;国内在该方 面的研究相对较晚,但发展迅速。王国辉等 [16] 采用 流体体积函数法模拟了一种旋流式喷嘴内部的气液 流动,并结合试验,发现改变喷嘴内部结构可以使 出口速度发生变化,而雾化锥角的变化只取决于旋 流器螺旋升角和旋流槽数量;张永良 [17] 利用试验和 数值计算,探讨了某些关键参数对传统离心式喷嘴 雾化效果的影响,而且表明利用流体体积函数法对 喷嘴雾化锥角的模拟与试验值有差异,需要对其进 行修正,但雾化锥角变化规律一致;吴高杨等 [18] 通 过试验和数值模拟研究了螺旋离心式喷嘴的雾化效 果,结果表明喷注压降和背压对液膜的一、二次破 碎有很大影响,而且背压对液膜锥角的影响明显小 于喷注压降;何志霞等 [19] …”
unclassified